2020
DOI: 10.1063/5.0019719
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the sensitivity of the two-temperature model for electron–phonon coupling measurements

Abstract: A crucial parameter in understanding hot electron physics is the electron–phonon (EP) coupling factor along with the governing physical relationships of the Two-Temperature Model (TTM) for electron thermalization. One of the most common ways to experimentally interrogate EP coupling is via ultra-fast optical excitement and thermoreflectance measurement. While there has been a significant amount of work using this method, there has been relatively little exploration of the sensitivity of the TTM to the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, the development of quasiparticle models for plasma-surface interaction is still in its infancy, as no studies have applied this strategy yet, to our knowledge. Inspiration can be taken from the two-temperature models frequently used to investigate electron-phonon coupling in laser-excited matter [125][126][127]. The so-called multi-plasma model (MPM) has recently been proposed as a generalized extension of these models, with the addition of plasmons, excitons and optionally molecular excitations [31].…”
Section: Class Iii: Mesoscopic Models -Computational Compromisementioning
confidence: 99%
“…However, the development of quasiparticle models for plasma-surface interaction is still in its infancy, as no studies have applied this strategy yet, to our knowledge. Inspiration can be taken from the two-temperature models frequently used to investigate electron-phonon coupling in laser-excited matter [125][126][127]. The so-called multi-plasma model (MPM) has recently been proposed as a generalized extension of these models, with the addition of plasmons, excitons and optionally molecular excitations [31].…”
Section: Class Iii: Mesoscopic Models -Computational Compromisementioning
confidence: 99%
“…It takes about 2 ps in Ni whilst it takes 8 ps in Au to obtain equality between the electronic and lattice temperatures. Naldo et al [40] performed a careful study of the sensitivity of TTM and showed the robustness of the predictions.…”
Section: Resultsmentioning
confidence: 99%